Modeling the Potential Productivity of Urban Agriculture and Its Impacts on Soil Quality Through Experimental Research on Scale-Appropriate Systems - Taylor, John R. (Frontiers in Sustainable Food Systems, 2020)
Urban agriculture could play a central role in local and regional food sovereignty in developed countries, but in many cities, a lack of space and competition with other land uses limit production. Options for meaningfully advancing food sovereignty goals include sustainable intensification of existing urban farms and gardens; 2) expansion of production into interstitial and other underutilized spaces undevelopable for other purposes; and 3) expansion of production in protected environments. Observational studies suggest that--like smallholder agriculture in the Global South--urban home, community, and market gardens in the developed world can be highly productive--but often are not. Scale-appropriate, agroecosystems-based research and outreach to urban agriculturalists are needed to help them grow more food, more sustainably. This replicated, long-term trial is addressing this need—and a dearth of experimental, normative research on urban agriculture—by evaluating the yield performance and impact on soil quality of four different systems of small-scale food production in Rhode Island, the second most densely populated state in the United States and a potential model for the development of sustainable urban food systems. Systems are modeled on vernacular systems in Providence, RI and Chicago, IL and on the scholarly and grey literature on sustainable intensification. They differ in soil management practices and nutrient sources. Results from the first three years of data collection indicate all four systems can be highly productive, with varying tradeoffs in terms of their sustainability and impacts on soil quality. While total marketable food yields were relatively modest compared to those reported in the grey literature for biointensive agriculture—2.22 to 2.96 kg m-2 averaged over three summer growing seasons compared to 4.64 kg m-2 for the “low end” of biointensive production—yields for individual crops exceeded—and often far exceeded—regional averages and, for most crops and systems, national averages, without a loss in soil quality. In addition to demonstrating the high productivity of small-scale systems compared to commercial farms, the study establishes a framework for conducting normative, experimental research that can help to guide practice. It also offers more reliable yield estimates for modeling the production potential of cities than do observational studies and agronomic experiments on monocultures.